Optimizing data retrieval latency in IoT through information centric in-network caching - Muhammad Ali Naeem; Meng Yahui; Ahmad Abrar (Alexandria Engineering Journal)
The integration of Information Centric Networking (ICN) with the Internet of Things (IoT) will meet the expectations of end users by providing an admirable network system. ICN enhances the IoT by utilizing in-network caching regarding data dissemination with the help of various paths labeled by the name of the path by which the data is returned. Caching is a significant technique for improving content accessibility, reducing hops while transferring data, and finally shortening data access time, which in turn improves IoT networks. This study develops a novel caching strategy that caches content in suitable locations at highly requested nodes, thereby improving the information caching efficiency of ICN-based IoT systems. When comparing the proposed caching scheme with other caching methods, it pay attention to the data retrieval latency, cache hit ratio, and the average number of hops. These results consistently show that the proposed strategy enhances cache performance by a high margin. The future context of the utilization of the specified caching strategy will lie in the advancements of fog, edge, and ad hoc networks concerning the concept of IoT and new trends like 5 G and 6 G.